ANALYSIS OF FACTORS INFLUENCING THE DECISION TO USE PAYLATER IN NORTH SUMATRA, WITH THE INTENTION TO USE AS AN INTERVENING VARIABLE - Harahap, Siti Khodijah; Saparuddin; Rahmi Syahriza (International Journal of Cultural and Social Science, 2025)
This study aims to analyze the influence of perceived usefulness, perceived ease of use, and attitude on the decision to use PayLater in North Sumatra, with willingness to use as an intervening variable. Data was obtained from 100 respondents thru a survey and analyzed using path analysis with SPSS 25 based on the Technology Acceptance Model (TAM) framework. The research results show that perceived usefulness and ease of use do not significantly affect the intention to use, while attitude has a significant positive effect. In the usage decision model, perceived usefulness has no significant effect, perceived ease of use has a significant negative effect, and attitude and intention to use have a significant positive effect. Mediation analysis shows that intention to use does not mediate the influence of perceived usefulness and ease of use, but partially mediates the influence of attitude on usage decision. This finding confirms that a positive attitude toward PayLater strengthens the intention and actual decision to use it, and reinforces the TAM concept, which emphasizes the importance of affective and behavioral intention factors over cognitive factors.